TOPICAL ISSUES OF CREDIT MARKET DEVELOPMENT IN UZBEKISTAN (European Journal of Economics, Finance and Business Development, 2026)
The credit market is one of the main segments of the national financial market. It ensures the flow of credit resources, and credit is an important factor in ensuring economic growth while maintaining macroeconomic stability. This article identifies current issues related to the development of the credit market in Uzbekistan and develops research proposals aimed at addressing these challenges. Specifically, it substantiates the need to develop the credit market by improving the credit market regulation system and reducing the state's share in the regulatory capital of commercial banks.